1989
DOI: 10.1103/physrevb.40.8075
|View full text |Cite
|
Sign up to set email alerts
|

Electron-spin resonance of the two-dimensional electron gas in Ga0.47In0.53As-InP heterostructures

Abstract: The microwave-induced change of the magnetoresistivity of Gao.47In0. 53As-InP heterostructures reveals resonant structure which is attributed to electron-spin resonance of the two-dimensional conduction electrons. With microwave frequencies up to 480 GHz and in magnetic fields up to 12 T, we studied the spin splitting of the two lowest Landau levels in different samples. The spin splitting of these Landau levels is a quadratic function of the magnetic field and its extrapolation to zero magnetic field leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 14 publications
5
28
0
Order By: Relevance
“…It has been previously demonstrated that high sensitivity can be obtained if the ESR absorption is detected electrically via a change induced in the magnetoresistance that can be observed under certain conditions in the regime of the quantum Hall effect [2]. This method has been successfully used in the analysis of the magnetic field dependence of the bare electron g-factor [3,4,5], the electron-nuclear interaction and nuclear-spin relaxation rates as a function of magnetic field [6] and the g-factor dependence on the top-gate voltage [7]. Although a variety of applications of EDESR have been demonstrated in quantum Hall systems, there have been no previous reports describing the underlying physics of the electrical response to ESR transitions in a 2DES.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that high sensitivity can be obtained if the ESR absorption is detected electrically via a change induced in the magnetoresistance that can be observed under certain conditions in the regime of the quantum Hall effect [2]. This method has been successfully used in the analysis of the magnetic field dependence of the bare electron g-factor [3,4,5], the electron-nuclear interaction and nuclear-spin relaxation rates as a function of magnetic field [6] and the g-factor dependence on the top-gate voltage [7]. Although a variety of applications of EDESR have been demonstrated in quantum Hall systems, there have been no previous reports describing the underlying physics of the electrical response to ESR transitions in a 2DES.…”
Section: Introductionmentioning
confidence: 99%
“…37 For the g factor a value of −4 was assumed. 38 The value of E F,2D was taken as the zero field value of the quantum wire Fermi energy E F,1D , which should be a good approximation for wire structures with a larger number of occupied levels. In principle, the carrier confinement in the wire can be characterized by the oscillator frequency 0 if a harmonic confinement potential is assumed.…”
Section: Simulationsmentioning
confidence: 99%
“…Second, the bare g-factor is expected to be very large. For instance the bare gfactor measured by electron spin resonance was found at around -5 in In 0.53 Ga 0.47 As [3] while effective g-factors g * (renormalized by electron-electron interactions) with absolute values between 14 and 28 were recently suggested from magneto-transport data [4,5]. The large resulting Zeeman spin splitting under the application of weak magnetic fields makes this semiconductor system a promising candidate for spin-valve mesoscopic devices working at relatively high temperatures [6].…”
Section: Introductionmentioning
confidence: 99%